THE INFLUENCE OF COMPETENCE AND ORGANIZATIONAL CULTURE ON THE PERFORMANCE OF MASSILA VILLAGE EQUIPMENT, PATIMPENG DISTRICT, BONE DISTRICT - Iskandar, Muh. Resky; Risman, Risman (Jurnal Manajemen Dan Bisnis, 2024)
The purpose of this research is to determine the effect of competency on the performance of the village apparatus in Massila, Patimpeng District, Bone Regency. To examine the effect of organizational culture on the performance of the village apparatus in Massila, Patimpeng District, Bone Regency. To analyze the simultaneous (together) effect of competency and organizational culture on the performance of the village apparatus in Massila, Patimpeng District, Bone Regency. This study uses quantitative analysis on the data collected, including reliability testing, normality testing, multicollinearity testing, heteroscedasticity testing, regression analysis, and coefficient of determination testing, which includes F-test and T-test. The data analysis technique used is multiple linear regression analysis, which aims to test the research hypotheses. Based on the hypothesis testing results, both simultaneously and partially, it was found that competency and organizational culture have a positive and significant impact on the performance of the village apparatus in Massila, Patimpeng District, Bone Regency.